Long-term low-dose atorvastatin therapy and prevention of macroangiopathy complications in elderly patients with Type 2 diabetes mellitus - G. A. Batrak; S. E. Myasoedova (Кардиоваскулярная терапия и профилактика)
Aim. To study the effectiveness of long-term low-dose atorvastatin therapy in elderly patients with Type 2 diabetes mellitus (DM-2) and dyslipidemia (DLP). Material and methods. In total, 135 elderly patients with DM-2 and DLP were included in the main group (MG), receiving atorvastatin (10—20 mg/d; mean dose 15,3 mg/d) for 5 years. The control group (CG) included 55 elderly patients with DM-2 and DLP, who received lipid-lowering diet only. Lipid profile and intima-media thickness (IMT) of brachio-cephalic and lower extremity arteries (Duplex scanning) were assessed at baseline and 5 years later. Results. During the five-year follow-up period, MG demonstrated improved lipid profiles, with target lipid levels achieved in 68 % of the patients receiving atorvastatin in the dose of 20 mg/d. Brachio-cephalic IMT was relatively stable (1,23±0,2 mm and 1,22±0,01 mm, respectively, at baseline and 5 years later). In CG, lipid levels remained high, brachio-cephalic IMT increased from 1,25±0,23 mm at baseline to 1,35±0,23 mm 5 years later (p<0,001), and lower extremity IMT increased from 1,21±0,14 mm to 1,45±0,12 mm, respectively (p<0,001). Conclusion. Long-term low-dose atorvastatin therapy improved lipid profile in elderly patients with DM-2 and DLP. Among those receiving atorvastatin in the dose of 20 mg/d, target lipid levels were achieved in 68 %. The therapy also prevented progressing of brachio-cephalic and lower extremity macroangiopathy, was safe and well tolerated.